Financing alternatives of budget deficit in Algeria 2014-2018: Analytical study - AROUS , Nesrine (Milev Journal of Research and Studies, 2020)
This study aimed to clarify the most important financing alternatives that have been adopted by different governments in Algeria since the decline of oil prices in 2014. This period was accompanied by the start of the application of expansionary monetary policies wich called “unconventional financing”. The study concluded that the resource regularization fund is the most important source of financing for the public budget deficit, and that there is an increase in exceptional revenues represented by the distributions of Bank of Algeria, In addition to the unconventional financing, the bond loan and bank financing are financing solutions in the past two years.